MON-925 A Wolf in Sheep’s Clothing: Intermittent Hypercalcemia from an Intrathyroidal Parathyroid Carcinoma - Trejo, Jonathan (J Endocr Soc, 2020)
Parathyroid carcinomas have an estimated prevalence of <0.1% of all cancers and is found in <1% of patients with primary hyperparathyroidism (PHPT). While they frequently present with PTH- mediated hypercalcemia, they are often distinguished by severe hypercalcemia and markedly elevated PTH levels compared to their benign counterparts. Parathyroid cancers most often arise from existing parathyroid glands, making them identifiable with standard imaging modalities such as parathyroid sestamibi scan, thyroid ultrasound, and 4-D CT scan. There are reports of non-functioning parathyroid carcinomas, including those that are intrathyroidal. Most of the reported cases are found de novo. We present a case of an intrathyroidal parathyroid carcinoma with intermittent hypercalcemia. A 72-year-old man with a history of Graves’ disease and RAI ablation in the 1970’s was found to have hypercalcemia up to 14.1 mg/dL (8.5 - 10.1) with a PTH level of 223 pg/mL (14 - 64). He denied any constipation, bone pain, fractures, renal stones, or changes in mental status. Thyroid ultrasound demonstrated a 3.9 cm R lobe complex nodule reported as TI-RADS 4, and a hypoechoic 1.0 cm nodule in the L lobe. No definitive parathyroid adenoma was reported. A parathyroid sestamibi scan showed persistent uptake in area of the L 1.0 cm nodule favoring a PTH adenoma while the R nodule had initial radiotracer uptake with delayed washout but no technetium uptake. Laboratory evaluation demonstrated a 24-hour urinary calcium of 338 mg/24hr, low 25-OH vitamin D, and normal vitamin D 1,25 levels. Osteoporosis was diagnosed by BMD with T-score of -3.2 at the femoral neck. Repeat serum corrected calcium level was 9.7 mg/dL and PTH was 93 pg/mL. FNA cytology of the R thyroid mass was reported as benign thyroid tissue. Due to size of the R thyroid nodule, the patient underwent a R hemithyroidectomy with L parathyroidectomy. Intraoperative PTH levels decreased from 154 to 120 pg/mL after removal of L parathyroid adenoma; PTH level decreased further to 12.9 pg/mL after R hemithyroidectomy. Surgical pathology revealed 4.5 cm R parathyroid carcinoma without thyroid tissue with positive margins, and a hypercellular L parathyroid gland. PHPT resolved. After review of all aspects of the case and discussion with patient, the decision was made to monitor his calcium and PTH levels and repeat BMD 1 year from resection. This is an uncommon presentation of a rare endocrine malignancy. To our knowledge, there are few case reports of non-functional parathyroid carcinomas that were initially reported as thyroid cancer or benign thyroid tissue after biopsy. This report underscores the importance in keeping this rare diagnosis in the evaluation of PTH-mediated hypercalcemia.